Influence of Is Amount of Channeling of Credit to Profit Bank Credit People Bank of Millenia in Manado (Study Case in The Year 2014-2018) - Alzefin Yolandi Roos Mareike Sinolungan (Journal of International Conference Proceedings (JICP), 2018)
"Bank is activity financial institution the core important mustering fund of society and channeling it return to society. Activity of fund gathering of this society can in the form of saving, deposit, giro, and others. In activity of channeling of fund to society can in the form of invesment / credit". Bank Credit People (BPR) is: (a).Fund mustering of society in the form of deposito, saving expect, certificate of saving, in the form of: giro, deposito/other form,(b).Giving Defrayal,(c).Providing and location of fund pursuant to law principle pursuant to specified by Indonesia Bank; it is fund, (d).Placing of Certificate Indonesia Bank form, time deposit,certificate of deposito,other bank saving. Target of giving credit:(1). Follow governmental program success in economic area and development. (2). Improving corporate activity so that can run function,usefull guarantee fulfilled of requirement of society. (3). Obtaining profit so that continuity of well guaranteed company life and can extend its effort. Credit function in life of economics: (a). Improve useful power of capital, (b). Power an good’s. (c). Economic stability, (d). Credit as bridge to increase earnings of national. Credit aid used by all entrepreneur to enlarge volume of is effort its production. Make-Up of effort expected will improve profit, where if advantage cumulatively developed in word meaning returned into capital structure, hence improvement will take place continuously and result earnings increasing. Element in giving of credit:(a). Trust, (b). Time, (c). Level Risk, (d). Achievement. Profit: difference between result of earnings and all expense of in certain accounting period. Profit type: (1). Gross Profit, (2). Profit is Effort, (3). Profit Cleanness In profit report/ lossy show classification in stimulating of measurement of profit: (1). Profit dirty of sale, (2). Operate for company. (3). Before Iease cutting, (4). Dirty after Iease cutting. Conclusion: amount of credit influence positive influence bank profit and significant. In obtaining maximal profit need the amount of credit channeled to mount each; every moment. Bank profit influenced by amount of credit, by another factor do not check. Result of research obtained by research of technique hypothesis test analyses correlation: existence of positive influence and significant between Amount of Credit with Profit Bank of BPR (Bank of Millenia) in Manado. Coefficient of Determines equal to 97% Profit Bank variable Year 2014-2018 influenced by It is Amount variable on him 3 % explained by other variable outside variable of is Amount of Credit do not be discussed in this research. Relation of is Amount of Credit to Profit Bank of Millenia) in Manado) obtained: r = these 0,98 matters show positive relation both variable, where amount of credit very determining in improving Profit. Conclusion: (1). Amount influence Profit Bank of BPR (Bank of Millenia) in Manado: positive influence and significant, showing maximal profit need the amount of Credit channeled to mount every moment. (2). Profit Bank by Amount of Credit by another factor do not check. Suggestion:(1). Research this expected to add reader side knowledge due to study of science finance-related and banking, (2). For research hereinafter, better be conducted by research of continuation use another indicator or variable. Keyword: Channeling of Credit, Profit Bank